What is the Contribution of Local Original Revenue to Regional Financial Independent? - Sari, Purnama; Garvera, R. Rindu; Sihabudin, Aan Anwar (JPAS (Journal of Public Administration Studies), 2018)
As a manifestation of decentralization, the purpose of local original revenue is to give authority to local governments to fund the implementation of regional autonomy in accordance with regional potential. With the regional autonomy policy, all regions are expected to be able to maximize their financial capabilities so that they can fund all government affairs in the regions independently. The purpose of this study was to analyze the contribution of local original revenue to regional financial independence. The research method used is a descriptive method with a quantitative approach, where the research was conducted on the Regional Financial Management Agency of Ciamis Regency. Even in this study will compare the results of research conducted in several other regions in Indonesia as well as in several regions in other countries. The results showed that the contribution of regional local revenue to regional financial independence in Indonesia was still low. The same conditions in several countries in Africa and Europe, where regions are still dependent on funds transferred from the central government, to carry out development and services to other publics